2010
DOI: 10.1007/s10546-009-9461-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Airflow Across Trees in a Windbreak

Abstract: The flow across a three-dimensional (3-D) windbreak comprising individual cypress trees is studied to establish the significance and extent of the 3-D flow patterns. The cypress tree is modelled as a solid cylindrical stem and a conic porous canopy. Cases with a single row of trees or two rows of trees with different distances between the rows are considered; in the case of a single row, several densities of the canopy are used. The steady Reynoldsaveraged Navier-Stokes (RANS) approximation is solved using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…For a windbreak with porosity similar to that featured in the present study, air flow in the lower part of the canopy was inclined upward to the upper part, whereas a large-scale recirculation zone was not observed (Gross, 1987;Melese et al, 2009;Rosenfeld et al, 2010). This flow features different from the present study is mainly caused by the configuration of a real three-dimensional (3-D) tree.…”
Section: Flow Characteristicscontrasting
confidence: 43%
See 1 more Smart Citation
“…For a windbreak with porosity similar to that featured in the present study, air flow in the lower part of the canopy was inclined upward to the upper part, whereas a large-scale recirculation zone was not observed (Gross, 1987;Melese et al, 2009;Rosenfeld et al, 2010). This flow features different from the present study is mainly caused by the configuration of a real three-dimensional (3-D) tree.…”
Section: Flow Characteristicscontrasting
confidence: 43%
“…For an accurate understanding of the shelter effect of natural windbreaks, windbreak of non-uniform porosity with finite thickness should be investigated systematically. This kind of demand on basic academic research has been mentioned by many researchers (Wang et al, 2001;Zhou et al, 2004;Rosenfeld et al, 2010). To our knowledge, however, no attempt has been made to conduct an in-depth investigation of windbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson [18] analyzed the use of several models, and concluded that results are nearly insensitive to the turbulence model. The turbulence model chosen for this study, as available in the commercial software, has its standard formulation, and then does not includes the extrasource terms [11,13], necessary to account for the influence of vegetation on the turbulence budget, as used by Rosenfeld et al [10].…”
Section: Computational Modelingmentioning
confidence: 99%
“…The RNG k-ε turbulence model was judged to be suitable to compute the separated shear flow (Kim et al, 1997). Airflow is assumed to be viscous, incompressible, isothermal, and steady (Chen et al, 2012), and the governing equations used to determine the continuous flow are as follows (Rosenfeld et al, 2010).…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%